IMPLEMENTASI KEBIJAKAN PROGRAM ALOKASI DANA KAMPUNG (ADK) - Muzaki, Kahar; Yuliani, Febri; Farida, Lena (Jurnal Ilmu Administrasi Negara, 2018)
Policy Implementation Program Village Fund Allocation. This study aims to analyze and describe and to determine the factors that affect the implementation of program policies Village Fund Allocation in the village Lubuk Dalam Subdistrict Siak. This type of research is using qualitative descriptive research. Data collected through observation, documentation, and interviews with informants have been. The study concluded that the implementation of program policies Village Fund Allocation in the village Lubuk Dalam Subdistrict Siak not run well. Where in the preparation of the action plan does not involve village consultative body, and in making the accountability report is still experiencing then the factors that affect the implementation of that communication, disposition, bureaucratic structure has worked well the constraints dalah resources, which still lack the educational background program implementers village Fund Allocation. And in the achievement of policy goals village fund allocation program in reducing poverty and in increasing production and productivity of the village community is also not optimal.